The prevalence and determinants of social media usage among medical students of Nishtar Medical University, Multan - Tufail, Nadia; Owais, Muhammad; Abbas, Aisha; Mushtaq, Fariha; Bint-e-Mansoor, Hafsa; Nadir, Muhammad (International Journal Of Community Medicine And Public Health, 2025)
Background: Social media platforms such as Instagram, Facebook, Snapchat and their usage has a significant prevalence in the medical students. Social media usage affects the quality of life and work of population including medical students, detrimentally affecting their mental health and academic performance. Methods: A cross-sectional study using non-random convenient sampling technique was conducted from March 5, 2024 to September 14, 2024 among the medical students of Nishtar Medical University, Multan. Data collection was done by a self – developed questionnaire. SPSS-27 was used to analyze data. Results: Out of 309 participants, 97.4% (301) students reported using social media, while only 2.6% (eight students) indicated that they did not use social media. First year medical students had the Social Media usage rate of 97.5% while the final year students had the highest social media usage rate of 100%. The most preferred social media platforms were Instagram (67.3%), followed by Facebook (24.6%) and Snapchat (8.1%). There was no statistically significant association between gender and prevalence of social media usage (p=0.183). Both male and female students showed a similar pattern of usage with 97.7% of males and 96.5% of females being active on social media. Conclusions: The study reveals that MBBS students, particularly Instagram, frequently use social media for both social and academic purposes. They spend significant time on these platforms daily and while they are essential for social and academic purposes, overuse of these platforms can hinder their learning and participation in extracurricular activities.